Granulocyte colony-stimulating factor impairs CD8+ T cell functionality by interfering with central activation elements. (13th May 2016) - Bunse, C E; Tischer, S; Lahrberg, J; Oelke, M; Figueiredo, C; Blasczyk, R; Eiz-Vesper, B
Summary: Besides mobilizing stem cells into the periphery, granulocyte colony-stimulating factor (G-CSF) has been shown to influence various types of innate and adaptive immune cells. For example, it impairs the effector function of cytotoxic T lymphocytes (CTLs). It is assumed that this effect is mediated indirectly by monocytes, regulatory T cells and immunomodulatory cytokines influenced by G-CSF. In this study, isolated G-CSF-treated CD8 + T cells were stimulated antigen-dependently with peptide–major histocompatibility complex (pMHC)-coupled artificial antigen-presenting cells (aAPCs) or stimulated antigen-independently with anti-CD3/CD28 stimulator beads. By measuring the changes in interferon (IFN)-γ and granzyme B expression at the mRNA and protein level, we showed for the first time that G-CSF has a direct effect on CD8 + CTLs, which was confirmed based on the reduced production of IFN-γ and granzyme B by the cytotoxic T cell line TALL-104 after G-CSF treatment. By investigating further elements affected by G-CSF in CTLs from stem cell donors and untreated controls, we found a decreased phosphorylation of extracellular-regulated kinase (ERK)1/2, lymphocyte-specific protein tyrosine kinase (Lck) and CD3ζ after G-CSF treatment. Additionally, miRNA-155 and activation marker expression levels were reduced. In summary, our results show that G-CSF directly influences the effector function of cytotoxic CD8 + T cells and affects various elements of T cell activation.